On the Three-Dimensional Contact Problem of a Rigid Inclusion Pressed Between Two Elastic Half-Spaces - Damen, G.M.J. (Engineering Transactions, 1977)
An approximation solution is found for the three-dimensional contact problem of two elastic half-spaces pressed against each other with a rigid inclusion between them. We confine ourselves to identical spaces nad will examine an inclusion of a such a nature that rotational symmetry is achieved.We apply asymptotics to a small parameter which is the quotient of the radius of the contact region with the inclusion and of the radius of the region where the spaces touch each other. These quantities can be compouted if the pressure at infinity and the geometry of the inclusion are given. After solving this part of the problem the surface pressure may be obtained.Numerical results are given for the small parameter and the surface pressure.